KING ARTHUR'S ROUND TABLE REVISITED: A REVIEW OF TWO RIVAL INTERPRETATIONS OF A HENGE MONUMENT NEAR PENRITH, IN CUMBRIA. (20th September 2019) - Leach, Stephen
Abstract : In 1937 R G Collingwood carried out an excavation at King Arthur's Round Table, a henge monument near Penrith. He wished to test the hypothesis that this may once have contained a circle of upright stones or wooden posts. His interim report, published in 1938, suggested that, on the evidence of excavation, this indeed might well have been the case. Unfortunately, illness prevented Collingwood returning to the site in 1938. In 1939 a second season of excavation was conducted under the direction of Gerhard Bersu. Bersu dismissed all of Collingwood's interpretations. He argued that there were no post-holes, and that the artificial surface seen by Collingwood was in fact entirely natural. And there the matter has rested – with most later commentators, such as Richmond, Hodder and Bradley, favouring Bersu's interpretation of the site and only a small minority, including Grace Simpson (the daughter of F G Simpson who worked with Collingwood on Hadrian's Wall), favouring Collingwood's. The present review of the two rival interpretations is occasioned by the discovery of a previously unpublished letter in which Collingwood gives his response to Bersu's interpretations. The author argues that in fact the balance of probability greatly favours Collingwood's interpretation rather than Bersu's.